The peril of stress in aviation safety - Oukil, Hamama (Journal of Human Sciences, 2021)
Working in air navigation sector is as interesting as it is difficult and complicated. The technological change that this important field entails and the modernization of the system and equipment it uses, encourage not only the rationalization of procedures and their application, but also to take into account the risk factors that may hinder the work of operating personnel.  It should be noted that the pilot and the air traffic controller are engaged in an extremely complex task involving verbal exchanges of information and instructions, wherestress is controlled on board, which is extremely dangerous due to the impact of this energy consumer on the physical and moral health of operating personnel.Indeed, a psycho-physiological reaction to a stimulus that caused the tension   involves a change in the metabolism of the professional, which the brunt on the safety of passengers, aircraft and air navigation installations is extremely perilous. Hence the need to establish a stress assessment discipline for operating personnel in order  to take in hand and clean up the causes of this energy-consumer.